2020
DOI: 10.24127/ajpm.v9i1.2157
|View full text |Cite
|
Sign up to set email alerts
|

Model Discovery Learning Untuk Meningkatkan Kemampuan Pemecahan Masalah

Abstract: Penelitian ini bertujuan untuk meningkatkan kemampuan pemecahan masalah matematis siswa pada materi pokok kubus dan balok dengan model Discovery Learning. Penelitian ini dilakukan di SMP PGRI Kasihan. Teknik pengumpulan data menggunakan observasi dan tes. Teknik analisis data dalam penelitian ini adalah dengan menelaah seluruh data, baik data kualitatif maupun data kuantitatif dari berbagai sumber yaitu hasil observasi, tes tertulis, dokumentasi, dan catatan lapangan. Berdasarkan hasil penelitian dapat disimpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…The research was dominated by 8th grade of junior high school, for example the problem found in the research conducted by Jana and Fahmawati (2020) that students' mathematical problem solving abilities were still very low. Students are still very difficult to work on problems in the form of problems.…”
Section: Research Subjects Assessment Of Students' Mathematical Probl...mentioning
confidence: 99%
See 2 more Smart Citations
“…The research was dominated by 8th grade of junior high school, for example the problem found in the research conducted by Jana and Fahmawati (2020) that students' mathematical problem solving abilities were still very low. Students are still very difficult to work on problems in the form of problems.…”
Section: Research Subjects Assessment Of Students' Mathematical Probl...mentioning
confidence: 99%
“…The study was dominated by 8th grade of junior high school because many mathematical problems were found at the 8th grade junior high school level, for example the problems found in the research conducted by Jana and Fahmawati (2020) that students' mathematical problem solving abilities were still very low. Students still have difficulty working on problems in the form of problems (Parlina, Septian, & Inayah, 2021;Septian, Komala, & Komara, 2019).…”
Section: Research Subjects Assessment Of Students' Mathematical Probl...mentioning
confidence: 99%
See 1 more Smart Citation
“…It will make student to think critically, logically, creatively indispensable in dealing with the development of society (Istikomah & Jana, 2019). Problem solving is the ability and knowledge that is central to teaching and learning activities in mathematics (Jana & Fahmawati, 2020;Usman, 2014). According to the Big Indonesian Dictionary, understanding comes from the word understanding, which means the process, method, act of understanding or understanding (Fitriani & Maulana, 2016).…”
Section: Problem Solving Abilitymentioning
confidence: 99%
“…Model guided discovery learning mengarahkan siswa ikut aktif berpartisipasi dalam pembelajaran sehingga dapat memperkuat konsep belajar (Mahanani, Rahayu, & Fajaroh, 2019) dan membantu siswa dalam meningkatkan keterampilan pemecahan masalah matematika (Jana, Anisa, & Fahmawati, 2020). Selain itu, penelitian Hasugian (2018) memiliki hasil bahwa model guided discovery learning efektif ditinjau dari prestasi belajar siswa.…”
Section: Pendahuluanunclassified